THE ROLE OF MANAGERIAL ACCOUNTING IN MAKING THE PRICING DECISION - Dr. Fatemeh darogheh hazrati; Angham Awad Kanawi Al Sawafi; Hajir Abdulameer Enayma Al- Farhan; Sabah Saadoon Abd Ali Kati Al Shgaen; Rasha Talib Jabbar Fahd Al_Hamd (Scholar Express Journals, 2022)
The study aimed at managerial accounting and its importance, where management accounting from the project contributes and helps the management in the implementation of the project's work, in addition to clarifying many quarters of experience in research and development processes. The reality of using traditional and modern management accounting methods, as well as their role in making decisions, has been identified, and the concept of decision is in fact a choice between a set of solutions to a problem or a crisis in the conduct of a particular work. We pay attention and study it, while others come out randomly without studying. The pricing decision is one of the most important administrative decisions due to its impact on the profitability of the facility in the short and long term. Therefore, the development of cost systems has become a vital matter that should be dealt with objectively and scientifically to reach rational decisions in this field. Through this research, the concept of pricing and Its objectives and methods represented by pricing on the basis of demand, pricing on the basis of competition, and pricing on the basis of cost
Keywords: Management accounting; management accounting methods; decision-making; the nature of pricing